The Role of Government and Local Communities in Sustainable Tourism Development through the Tourism Village Concept Applied in Tomohon City - Neni Kumayas; Djefry Deeng; Nasrun Sandiah (Dinasti International Journal of Education Management And Social Science, 2025)
Sustainable tourism development in Tomohon City, a prominent destination in North Sulawesi, faces challenges such as limited infrastructure, suboptimal community participation, and fragmented environmental management. This study examines the roles of the government and local communities in supporting sustainable tourism through the tourism village concept. The research employs a qualitative case study method, focusing on five urban villages in Tomohon City with significant tourism potential and community involvement. Data collection involved in-depth interviews with government officials, tourism actors, and local communities, as well as field observations and document analysis of tourism policies and programs. Data were analyzed through reduction, presentation, and conclusion drawing. Findings reveal the government plays a strategic role in policy formulation, community empowerment, and infrastructure development, but implementation is hindered by budget limitations and inter-agency coordination. Local communities contribute through culture- and environment-based tourism management, such as homestays, handicrafts, and tradition preservation. Participation increases with support from government or NGOs but remains uneven. Synergies between stakeholders are observed in tourism training, cultural festivals, and environmental initiatives, yet require enhanced communication and systematic empowerment. This study concludes that sustainable tourism village development in Tomohon City relies on synergistic collaboration, inclusive policies, and active community participation to serve as a model for other regions.